PENGUATAN PROGRAM LITERASI DASAR AL-QUR'AN MELALUI METODE IQRO KELAS 1 DI MIS MIFTAHUL HUDA 2 KOTA PALANGKA RAYA - Muhammad Tabrani; Yulia Rahmah; Susi Winarti (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2024)
This service aims to strengthen basic Al-Quran literacy in MIS Miftahul Huda 2 students in grade 1 through the Iqro method which is one of the very popular learning methods for reading the Al-Quran. Using a qualitative descriptive approach, this research aims to describe the effectiveness of the Iqro method basic literacy program in improving students' skills in understanding and reading the Al-Quran properly and correctly. Strengthening the basic Al-Quran literacy program using the Iqro method for grade 1 students is carried out using a gradual approach. The results of the service evaluation show that the basic literacy program using the Iqro method is able to improve students' understanding of the hijaiyah letters, recognizing the differences between points and harakat, and fluency in reading the Al-Quran, especially through a step-by-step approach that is adapted to the students' individual abilities. This growth is also supported by factors such as motivation, parent participation and teacher teaching.